THE AUDIT AUTHORITY OF THE STATE AUDIT BOARD ON THE VILLAGE FINANCIAL MANAGEMENT IN SOLOK REGENCY - Budiyono Budiyono; Yusdiyanto Yusdiyanto; Irdham Riyanda (Cepalo)
Village development is a critical focus in the third Nawacita, outlined in the 2020-2024 RPJMN. However, uncertainties persist concerning administrative law, particularly in the areas of institutional authority and mechanisms for examining village financial management. The State Audit Board of the Republic of Indonesia (BPK-RI), as the principal financial auditor, lacks a clear mandate under the current State Finance Law to audit village governance and finances. This research utilized normative and empirical juridical analysis methods to identify the necessary audit model for village governments. It was framed using theories of state finance, state financial audits, and authority. The findings indicate a need for legislative alignment between the Laws on State Finance and the Laws on Village Governance. The research concluded that the current authority granted to BPK-RI over village finances carries risks of arbitrary actions and potential lawsuits against BPK-RI. Furthermore, interviews with the Nagari government in Solok Regency highlighted that BPK-RI's audits have positively impacted performance enhancements in village governance. It was suggested that BPK-RI should concentrate on SPI audit models and the performance of the Nagari government. Therefore, an integrated audit model emerges as the ideal approach for effective oversight of village finances.